Seismic Risk Assessment of Wood Frame Construction Using Fuzzy Based Techniques - Ghorbani Komsari, Sajjad (Université d'Ottawa / University of Ottawa, 2014)
Wood-framed buildings have generally performed well during earthquake events, resulting in low fatality levels. However, various degrees of damage is still observed in these buildings during previous earthquakes. Lessons learned from the performance of wood frame construction in these earthquakes is led to an improvement in the design codes and construction practices over the past decades. But, the existing buildings are still vulnerable, since they were designed based on the older codes or constructed using old construction practices. Wood frame construction is the most common construction type in Canada, especially for single family dwellings. Most of these buildings are old, built prior to any modern seismic requirement, and have not been retrofitted against the damaging effects of earthquakes. Therefore, with a number of Canadians living in areas of high or moderate earthquake risk, there is a need to develop tools to assess the seismic vulnerability of the exiting wood-framed buildings in Canada. In the following thesis, a risk-based visual seismic assessment model and a screening tool (CanRisk) is developed, to assess the seismic vulnerability of existing wood frame construction in Canada. The model is dependent on the seismic hazard, building vulnerability, and building importance/exposure, which are integrated using hierarchical fuzzy rule based modeling. In the proposed seismic assessment model, fuzzy logic is used as a computing technique to capture the vagueness and uncertainty of a seismic vulnerability assessment, caused by subjectivity involved in the evaluation process. The hierarchical fuzzy rule based modeling used in this seismic assessment method is implemented in a prototype Matlab based program (CanRisk), which incorporates the Canadian seismic design practice based on the National Building Code of Canada (NBCC) and the Canadian site seismic hazard. A sensitivity analysis is conducted to test and verify the seismic assessment model and investigate the effects of various parameters on the outcome of the assessment. Also, in a case study, selected wood-framed buildings located in the city of Ottawa are evaluated using CanRisk, to demonstrate the applicability of the program.
Keywords: Earthquake risk assessment; Uncertainty; Fuzzy Logic; Decision-making; Retrofitting; Wood Frame Construction